Prevalence and Associated Factors of Hypertension: A Community-Based Cross-Sectional Study in a Rural Municipality of Eastern Nepal (Journal of Nobel Medical College, 2025)
Background: Hypertension is a major modifiable risk factor for premature mortality. The 2022 Nepal Demographic and Health Survey report a prevalence of about 20%, yet fewer than 5% of cases are adequately controlled, indicating major gaps in detection and management despite initiatives such as the Hypertension Care Cascade. Evidence from the limited studies in Nepal applying the ACC/AHA 2017 guidelines suggests that lower blood pressure cut-offs improve early identification of individuals at increased cardiovascular risk.Materials and Methods: A rural community-based cross-sectional study was conducted among 357 adults using multistage random sampling. Data were collected using a pre-tested questionnaire. Blood pressure was measured using standard procedures and classified according to the ACC/AHA 2017 guidelines.Results: The prevalence of hypertension was 52.1% (n=186). Among hypertensive participants, 61.3% were aware of their condition, 47.8% were receiving antihypertensive treatment, and 33.9% had controlled blood pressure. Age was significantly associated with hypertension (p=0.048), with a higher prevalence of stage 2 hypertension among those aged >60 years. Educational status showed a significant association (p=0.002), with higher prevalence among individuals with no formal education. Physical inactivity and smoking history (pack-years) were also significantly associated (p=0.040). Hypertension was more common among participants from joint or extended families (p=0.016), those reporting financial inadequacy (p